Una presentación atípica y grave de síndrome poliglandular autoinmune tipo 2 - Andrea Riaño Pérez; Carles García Cervera; Jorge Peris García; Vicente Giner Galvañ (Sociedade Galega de Medicina Interna, 2022)
Background: Recurrent pericarditis has been described as an unusual manifestation of autoimmune polyglandular syndrome type 2 (APS 2). Case report: We describe a case of a 44-year-old woman who was admitted to hospital due to 5 pericarditis, 3 of them with cardiac tamponade, and in the etiological study of this pathology she was diagnosed with an APS 2. Conclusion: The association of serositis with APS 2 is exceptional with less than 10 cases reported in the literature. The presence of recurrent pericarditis of unknown cause should make us consider APS 2 in the differential diagnosis.